Observation of the strain-driven charge-ordered state in La₀.₇Ca₀.₃MnO₃₋δ thin film with oxygen deficiency - Prokhorov, V.G.; Komashko, V.A.; Kaminsky, G.G.; Svetchnikov, V.L.; Zandbergen, H.W.; Lee, Y.P.; Park, J.S.; Kim, K.W. (Физика низких температур, 2003)
The magnetic and transport properties of La₀.₇Ca₀.₃MnO₃₋δ films with an oxygen deficiency (δ≃ 0.1) and a La₀.₉Ca₀.₁MnO₃ film with the stoichiometric oxygen content are investigated in a wide temperature range. It is shown that the charge-ordered insulating (COI) state is observed for a La₀.₇Ca₀.₃MnO₂.₉ film with thickness d ≤ 30 nm, which manifests mainly a cubic crystal structure with an anomalously small lattice parameter for this composition. An increase in the film thickness (d ≃ 60 nm) leads to a structural transition from the lattice-strained cubic to the relaxed rhombohedral phase, is accompanied by a shift of the Curie point (TC) to lower temperature and a frustration of the COI state. The magnetic and transport properties of the La₀.₇Ca₀.₃MnO₂.₉ film with d ≃ 60 nm are similar to those exhibited by the optimally oxygen-doped La₀.₉Ca₀.₁MnO₃ film. It is concluded that the formation of the COI state in the La₀.₇Ca₀.₃MnO₃₋δ compound is governed by a compression of the crystal lattice rather than accumulation of oxygen vacancies, the low doping of the substituted divalent ions, or electronic phase separation.